HISTOLOGICAL COMPARISON OF TWO STAINING METHODS IN IDENTIFICATION OF MYCOBACTERIUM TUBERCULOSIS IN GRANULOMATOUS LYMPHADENITIS - Ahmad, Fiaz; Rehman, Abdur; Jadoon, Omair (Journal of Ayub Medical College Abbottabad, 2018)
Background: Tuberculosis, among human bacterial infections is very important disease of modern world and disease has forensic importance. Extra pulmonary infection is also very common. Histopathology of effected tissue is an important diagnostic modality. Demonstration of mycobacterium tuberculosis in granulomas is necessary for definitive diagnosis of tuberculosis, as many different granulomatous diseases may mimic tuberculosis. Study was conducted to see the positivity of mycobacterium Tuberculosis in tuberculous lymphadenitis and comparative difference in two stains. Method: A correctional study on tuberculosis was performed in PGMI Lahore in collaboration with pathology department Ayub medical college Abbottabad. Fifty cases of formalin fixed paraffin embedded tissue block previously diagnosed as tuberculous lymphadenitis on histopathology were selected. Three-micron thick section were taken and stained with Zn stain and Auramin/ Rhodamin stain. The results were compared, statistical analysis was done using 2 by 2 table. Results: Out of 33(66%) female and 17(34%) male patients ranging from 9-80 years 9(18%) were positive for Mycobacterium Tuberculosis with Zn stain and 21 (42%) were positive in Auramine/ Rhodamine staining procedure. Conclusion: Auramine/ Rhodamine staining procedure was superior to Zn staining method for tissue staining of Mycobacterium Tuberculosis. Keywords: Mycobacterium tuberculosis; Auramin/Rhodamin stain; ZN stain